2016
DOI: 10.3390/fermentation2020009
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Two Saccharomyces cerevisiae Strains Affects Fermentation-Derived Compounds in Wine

Abstract: Previous winery-based studies showed the strains Lalvin ® RC212 (RC212) and Lalvin ® ICV-D254 (D254), when present together during fermentation, contributed to >80% relative abundance of the Saccharomyces cerevisiae population in inoculated and spontaneous fermentations. In these studies, D254 appeared to out-compete RC212, even when RC212 was used as the inoculant. In the present study, under controlled conditions, we tested the hypotheses that D254 would out-compete RC212 during fermentation and have a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…With wine, numerous studies have been carried out with non Saccharomyces yeasts, and most have focuses on improving or enriching of aroma profiles, whereas others have focused more on controlling the final product concentration of specific compounds, such as ethanol or acetic acid (Andorrà et al, 2012 ; Rantsiou et al, 2012 ; Medina et al, 2013 ; Contreras et al, 2014 ; Izquierdo Cañas et al, 2014 ; Zara et al, 2014 ; Canonico et al, 2015 , 2016 ; Rodrigues et al, 2016 ). However, fewer studies have been published about fermentation characterization by combining Saccharomyces strains or using uncommon Saccharomyces species (Cheraiti et al, 2005 ; Howell et al, 2006 ; King et al, 2010 ; Arroyo-López et al, 2011 ; Barrajón et al, 2011 ; Saberi et al, 2012 ; Williams et al, 2015 ; Gustafsson et al, 2016 ). Just as some of these investigations have suggested, our results showed that the final product composition of co-fermented musts cannot always be predicted from those of mono-fermentations.…”
Section: Discussionmentioning
confidence: 99%
“…With wine, numerous studies have been carried out with non Saccharomyces yeasts, and most have focuses on improving or enriching of aroma profiles, whereas others have focused more on controlling the final product concentration of specific compounds, such as ethanol or acetic acid (Andorrà et al, 2012 ; Rantsiou et al, 2012 ; Medina et al, 2013 ; Contreras et al, 2014 ; Izquierdo Cañas et al, 2014 ; Zara et al, 2014 ; Canonico et al, 2015 , 2016 ; Rodrigues et al, 2016 ). However, fewer studies have been published about fermentation characterization by combining Saccharomyces strains or using uncommon Saccharomyces species (Cheraiti et al, 2005 ; Howell et al, 2006 ; King et al, 2010 ; Arroyo-López et al, 2011 ; Barrajón et al, 2011 ; Saberi et al, 2012 ; Williams et al, 2015 ; Gustafsson et al, 2016 ). Just as some of these investigations have suggested, our results showed that the final product composition of co-fermented musts cannot always be predicted from those of mono-fermentations.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, usually, the articles considered the impact on volatile diversity of single strains or mixed starters composed of one S. cerevisiae strain and one non-Saccharomyces species. While the effect of multiple Saccharomyces yeast co-inoculations on volatile wine composition has been assessed (yeast inocula differed substantially in volatile thiols and other flavor compounds) [97,98], the interactions among different non-Saccharomyces wine yeast species need to be further elucidated [69]. The present findings suggest that the addition of M. pulcherrima to the coupled (in the case of the strains we tested) S. cerevisiae/T.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, recent studies on the dominance of different inoculated strains have mostly been carried out on mixed fermentations with non-Saccharomyces yeasts and S. cerevisiae with the aim of understanding the behavior and interactions of strains throughout the fermentation process [11][12][13][14]. Fewer studies have focused on the population dynamics of different inoculated strains of S. cerevisiae, as reported by Gustafsson et al [15]. Previous winery-based studies have shown that the frequently used strains Lalvin RC212 and Lalvin ICV-D254 tend to predominate, with over 80% presence even in spontaneous fermentations [16].…”
Section: Introductionmentioning
confidence: 99%